'A journal with ambitions': Health Libraries Review and Shane Godbolt. (30th November 2020) - Morgan, Peter
Abstract: In 1978, the UK Library Association's newly formed Medical, Health and Welfare Libraries Group decided to establish a newsletter for its members. This paper sets out to describe how that newsletter evolved into Health Libraries Review (subsequently Health Information and Libraries Journal) and became the premier European journal for health‐care information professionals. Drawing on both published accounts and personal reminiscences, it focuses on the role played by Shane Godbolt as the Review's founding editor. It analyses and discusses the factors that influenced her work, and concludes by summarising the lasting importance of her achievements as editor.